Clinical implications of coronavirus disease 2019 in neonates - Do-Hyun Kim (Clinical and Experimental Pediatrics, 2021)
Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019, a small number of coronavirus disease 2019 (COVID-19) cases in neonates have been reported worldwide. Neonates currently account for only a minor proportion of the pediatric population affected by COVID-19. Thus, data on the epidemiological and clinical features of COVID-19 in neonates are limited. Approximately 3% of neonates born to mothers with COVID-19 reportedly tested positive for SARS-CoV-2. Current limited data on neonates with COVID-19 suggest that neonatal COVID-19 shows a relatively benign course despite a high requirement for mechanical ventilation. However, neonates with pre-existing medical conditions and preterm infants appear to be at a higher risk of developing severe COVID-19. The greatest perinatal concern of the COVID-19 pandemic is the possibility of vertical transmission, especially transplacental transmission of SARS-CoV-2. Although direct evidence of the vertical transmission of SARS-CoV-2 is lacking, its possibility during late pregnancy cannot be ruled out. This review summarizes available case studies on COVID-19 in neonates and introduces what is currently known about neonatal COVID-19 with focus on its vertical transmission.